Working towards improved collaboration: reviewing provision and support for Christian parents/carers - Holmes, Sarah E. (British Journal of religious education, 2025)
It is increasingly acknowledged by a range of sectors, particularly health and educational, that collaboration with parents is fundamental to improving the developmental outcomes of children. It is also becoming more commonplace within the UK church and para-church organisations to emphasise the importance of supporting parents as they seek to nurture their child’s Christian faith. This raises multiple questions around the resourcing of institutions such as churches and school to form supportive, collaborative partnerships with parents for the sake of the children’s spiritual growth and development. This exploratory study collected data from three different perspectives: a review of tools and resources; interviews of practitioners and online surveys of parents in seventeen case-study contexts. In each arena, the provision and support for parents and carers for nurturing their Christian faith was investigated. Epstein’s types of involvement theory was used as a framework for analysis to map the nature of resources currently available for churches and faith-based schools wanting to collaborate with parents and carers, as well as to identify gaps and opportunities for future resourcing to enhance this kind of collaboration and partnerships.